A high surface area amorphous zirconium oxide catalytic material and preparation method thereof
By preparing amorphous zirconia catalytic materials with high surface area, and using ultrasonic and hydrothermal reaction techniques to form nanoscale copper nanocrystals and alloy interface species, the problem of structural instability in existing catalytic materials in reducing atmosphere is solved, and the effect of efficient catalytic reduction of CO2 to methanol is achieved.
Patent Information
- Application Number
- CN202111015117.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-08-31
AI Technical Summary
The microstructure of existing catalytic materials is unstable in reducing atmospheres, which can easily lead to reduced catalytic activity or inactivation, especially under high temperature conditions.
Using a preparation method of a high surface area amorphous zirconia catalytic material, the first contact reaction is carried out by ultrasonic dissolving zirconium nitrate and propylene oxide, followed by hydrothermal reaction and adding metal copper salts to perform the second and third contact reactions, forming a nanoscale copper nanocrystal and alloy interface species.
The thermal stability and catalytic activity of the catalyst are improved, and it can catalyze the reduction of CO2 and synthesize methanol at low temperatures, and it is cheap in preparation and easy to operate.
Smart Images

Figure BDA0003240083370000081 
Figure BDA0003240083370000091 
Figure HDA0003240083380000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials for hydrogenation to methanol, and particularly relates to an amorphous zirconium oxide catalytic material with a high surface area and a preparation method thereof. Background Art
[0002] Oxide-based porous materials are good carriers in the field of catalysis, but the preparation methods of high specific surface area materials still need further exploration. Copper (zinc / gallium)-based materials are widely used in catalytic reactions such as the hydrogenation of carbon dioxide to synthesize methanol, the catalytic conversion of water gas, the photocatalytic degradation of organic matter, and the elimination of automobile exhaust (NO, CO, etc.) due to their unique redox properties and high catalytic activity.
[0003] It is generally believed that the catalytic reaction mainly takes place on the copper surface. However, pure copper oxide is extremely unstable in microstructure in a reducing atmosphere. It is easy to turn into metallic copper and sinter at high temperatures, causing its exposed active area to decrease rapidly, resulting in a rapid decrease in catalytic activity or even inactivation.
[0004] Metals (such as copper, zinc, gallium, etc.) highly dispersed in porous oxide materials with high surface areas have been proven to be good redox reaction catalysts. Copper oxide, zinc oxide or gallium oxide has relatively high thermal stability. At the same time, because it is an active component or active additive for catalytic reactions such as synthesis gas and carbon dioxide hydrogenation to methanol, copper oxide and zinc oxide, zirconium oxide and other metals are added to amorphous zirconium oxide with a high specific surface area to form nano-scale copper nanocrystals and rich alloy / interface species, thereby increasing the stability of active species and the ability of the catalyst to catalyze the dissociation of hydrogen and activate carbon dioxide, which is beneficial to the carbon dioxide reduction reaction, thereby preparing a high-performance CO2 hydrogenation to methanol catalytic material.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for preparing an amorphous zirconia catalytic material with a high surface area, which has the advantages of low preparation cost, simple and safe operation, short reaction cycle, and good product repeatability. The amorphous zirconia catalytic material with a high surface area prepared by the method has the advantages of low cost, high catalytic activity, and high thermal stability. It can catalytically reduce CO2 to synthesize the hydrogen storage substance methanol with high selectivity under relatively low temperature conditions, and can be used in the fields of material research and catalytic hydrogenation of carbon dioxide to synthesize methanol.
[0007] The present invention is achieved by adopting the following technical solutions:
[0008] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0009] S1, adding zirconium nitrate to ethanol, dissolving it by ultrasonication, and then adding propylene oxide to carry out a first contact reaction to obtain a solution I;
[0010] S2, subjecting solution I to a hydrothermal reaction, and drying and crushing the resulting material to obtain amorphous zirconium oxide;
[0011] S3, adding amorphous zirconium oxide into water, dispersing by ultrasonication, adding at least one of a metal copper salt, a metal zinc salt, a metal gallium salt or a metal manganese salt, and performing a second contact reaction to obtain a solution II;
[0012] S4, adding an aqueous solution of ammonium carbonate to solution II to carry out a third contact reaction. After the reaction is completed, the obtained material is centrifuged, dried, crushed, and calcined to obtain an amorphous zirconium oxide catalytic material with a high surface area.
[0013] In a preferred embodiment, in step S1, the ultrasonic dissolution is performed at a frequency of 40-60 KHz for 25-40 min; in a further preferred embodiment, the ultrasonic dissolution is performed at a frequency of 50 KHz for 30 min;
[0014] In a preferred embodiment, in step S1, the molar ratio of propylene oxide and zirconium nitrate calculated as Zr element is (1.5-2.5):1; in a further preferred embodiment, the molar ratio of propylene oxide, ethanol and zirconium nitrate calculated as Zr element is (1.5-2.5):(60-70):1.
[0015] In a preferred embodiment, in step S1, the conditions for the first contact reaction are: temperature of 10-40°C, and time of 0.1-10 min; in a further preferred embodiment, the conditions for the first contact reaction are: temperature of 20-30°C, and time of 3-9 min; in a further preferred embodiment, the conditions for the first contact reaction are: temperature of 23-27°C, and time of 5-8 min.
[0016] In a preferred embodiment, in step S1, the first contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the first contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0017] In a preferred embodiment, in step S2, the temperature of the hydrothermal reaction is 100-200°C, and the time is 15-25h; in a further preferred embodiment, in step S2, the temperature of the hydrothermal reaction is 140-160°C, and the time is 18-20h; in a particularly preferred embodiment, in step S2, the temperature of the hydrothermal reaction is 150°C, and the time is 19h.
[0018] In a preferred embodiment, in step S3, the conditions of the second contact reaction are: temperature of 10-40° C. and time of 0.1-10 h.
[0019] In a preferred embodiment, the molar ratio of the metal copper salt calculated as Cu element to the amorphous zirconium oxide calculated as Zr element is (0-0.18):1; the metal copper salt is preferably copper acetate.
[0020] In a preferred embodiment, the molar ratio of the metal zinc salt calculated as Zn element to the amorphous zirconium oxide calculated as Zr element is (0-0.018):1; the metal zinc salt is preferably zinc acetate.
[0021] In a preferred embodiment, the molar ratio of the metal gallium salt calculated as Ga element to the amorphous zirconium oxide calculated as Zr element is (0-0.018):1; the metal gallium salt is preferably gallium nitrate.
[0022] In a preferred embodiment, the molar ratio of the metal manganese salt calculated as Mn element to the amorphous zirconium oxide calculated as Zr element is (0-0.018): 1. The metal manganese salt is preferably manganese nitrate.
[0023] In a preferred embodiment, the above-mentioned metal copper salt, metal zinc salt, metal gallium salt and metal manganese salt can be used in combination.
[0024] In a preferred embodiment, in step S3, the second contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the second contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0025] In a preferred embodiment, in step S4, the conditions for the third contact reaction are: temperature of 70-90°C, and time of 0.1-10h; in a further preferred embodiment, in step S4, the conditions for the third contact reaction are: temperature of 78-82°C, and time of 1-8h; in a particularly preferred embodiment, in step S4, the conditions for the third contact reaction are: temperature of 80°C, and time of 3-5h.
[0026] In a preferred embodiment, the ammonium carbonate aqueous solution is formed by dissolving ammonium carbonate in deionized water, and the concentration of the ammonium carbonate aqueous solution is 1-20 g / L; in a further preferred embodiment, the concentration of the ammonium carbonate aqueous solution is 5-15 g / L; in a further preferred embodiment, the concentration of the ammonium carbonate aqueous solution is 8-12 g / L; in a particularly preferred embodiment, the concentration of the ammonium carbonate aqueous solution is 9.6 g / L.
[0027] In a preferred embodiment, the molar ratio of ammonium carbonate to the metal copper salt calculated as Cu element is (1-2):1; the molar ratio of ammonium carbonate to the metal zinc salt calculated as Zn element is (1-2):(0-0.5); the molar ratio of ammonium carbonate to the metal gallium salt calculated as Ga element is (1-2):(0-0.5); the molar ratio of ammonium carbonate to the metal manganese salt calculated as Mn element is (1-2):(0-0.5).
[0028] In a preferred embodiment, in step S2, the drying conditions are as follows: temperature is 40-80°C and time is 2-24h.
[0029] Preferably, in step S4, the drying conditions include: temperature of 40-80°C, time of 2-24h; the calcination conditions include: temperature of 300-500°C, time of 0.5-8h.
[0030] In a preferred embodiment, in step S4, the centrifugal speed is 6000-8000 rpm; in a further preferred embodiment, in step S4, the centrifugal speed is 7000 rpm.
[0031] The beneficial effects of the present invention are:
[0032] 1. The preparation method of the present invention has the advantages of low preparation cost, simple and safe operation, short reaction cycle, good product reproducibility, etc.
[0033] 2. The high surface area amorphous zirconia catalytic material prepared by the preparation method of the present invention is a nano-scale copper nanocrystal, or a copper-zinc / gallium alloy species, which can increase the stability of active species, the catalyst's catalytic hydrogen dissociation activity and the ability to activate carbon dioxide, and is beneficial to the selective catalytic carbon dioxide reduction reaction.
[0034] 3. The high-surface-area amorphous zirconia catalytic material obtained by the preparation method of the present invention has the advantages of low cost, high catalytic activity, high thermal stability, etc. It can catalytically reduce CO2 to synthesize the hydrogen storage substance methanol with high selectivity under low temperature conditions, and can be used in the fields of material research and carbon dioxide catalytic hydrogenation to synthesize methanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 It is the XRD spectrum of the high surface area amorphous zirconia catalytic material prepared in Examples 1-7 of the present invention. DETAILED DESCRIPTION
[0037] The technical scheme in the embodiment will be described clearly and completely below in conjunction with the accompanying drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0040] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 5 min to obtain a solution I;
[0041] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0042] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 50 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0043] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0044] S5, taking the zirconium oxide aqueous dispersion, adding 0.0943 g of copper acetate monohydrate, and stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0045] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 1.5:1;
[0046] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green Cu / a-ZrO2 catalyst.
[0047] Example 2
[0048] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0049] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 45 min at a frequency of 40 KHz, propylene oxide was added to carry out a first contact reaction for 3 min to obtain a solution I;
[0050] S2, performing a hydrothermal reaction at 150°C for 24 hours, drying the obtained solid sol at 60°C for 28 hours, and then drying at 200°C for 6 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:70:2.5;
[0051] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0052] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0053] S5, taking the zirconium oxide aqueous dispersion, adding 0.1886 g of copper acetate monohydrate, stirring at 25° C. and 350 rpm for a second contact reaction for 1.5 hours;
[0054] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 5 hours; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 2.5:1;
[0055] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green Cu / a-ZrO2 catalyst.
[0056] Example 3
[0057] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0058] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 45 min at a frequency of 30 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0059] S2, performing a hydrothermal reaction at 150°C for 16 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:65:2;
[0060] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0061] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0062] S5, taking the zirconium oxide aqueous dispersion, adding 0.2358 g of copper acetate monohydrate, and stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0063] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 5 hours; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 2:1;
[0064] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green Cu / a-ZrO2 catalyst.
[0065] Example 4
[0066] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0067] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0068] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0069] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0070] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0071] S5, taking the zirconium oxide aqueous dispersion, adding 0.2829 g of copper acetate monohydrate, and stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0072] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 3:1;
[0073] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green Cu / a-ZrO2 catalyst.
[0074] Example 5
[0075] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0076] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0077] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0078] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0079] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0080] S5, taking the zirconium oxide aqueous dispersion, adding 0.3301 g of copper acetate monohydrate, and stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0081] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 3.5:1;
[0082] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green Cu / a-ZrO2 catalyst.
[0083] Example 6
[0084] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0085] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0086] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0087] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0088] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0089] S5, taking the zirconium oxide aqueous dispersion, adding 0.1886 g of copper acetate monohydrate and 0.1037 g of zinc acetate dihydrate, stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0090] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to (copper acetate monohydrate calculated as Cu+zinc acetate dihydrate calculated as Zn) is 1.5:1;
[0091] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green CuZn / a-ZrO2 catalyst.
[0092] Example 7
[0093] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0094] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0095] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0096] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0097] S4, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0098] S5, taking the zirconium oxide aqueous dispersion, adding 0.1886 g of copper acetate monohydrate and 0.1208 g of hydrated gallium nitrate, stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0099] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to (copper acetate monohydrate calculated as Cu+gallium nitrate hydrate calculated as Ga) is 1.5:1;
[0100] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green CuGa / a-ZrO2 catalyst.
[0101] Example 8
[0102] A method for preparing an amorphous zirconium oxide catalytic material with a high surface area comprises the following steps:
[0103] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0104] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0105] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0106] S4, taking the zirconium oxide aqueous dispersion, adding 0.1886 g of copper acetate monohydrate and 0.1356 g of hydrated manganese nitrate, stirring at 25° C. and 400 rpm for a second contact reaction for 1 hour;
[0107] S5, at 25°C, 0.0681 g of ammonium carbonate was dissolved in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0108] S6, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a third contact reaction for 3 hours; the molar ratio of the ammonium carbonate to (copper acetate monohydrate calculated as Cu+manganese nitrate hydrate calculated as Mn) is 1.5:1;
[0109] After the reaction is completed, the obtained substance is centrifuged at 7000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a high surface area amorphous zirconia catalytic material, which is a dark green CuMn / a-ZrO2 catalyst.
[0110] Test Example 1
[0111] The high surface area amorphous zirconia catalytic materials (hereinafter referred to as catalytic materials) prepared in Examples 1 to 8 were tested for specific surface area and pore size by Micromeritics ASAP-2010 specific surface area and pore size distribution tester. The test results are shown in Table 1.
[0112] Table 1 Test results of catalytic material performance obtained in Examples 1 to 8
[0113]
[0114] As can be seen from Table 1, the high surface area amorphous zirconium oxide catalytic material prepared by the present invention has a specific surface area of up to 154.5 m 2 / g, which can effectively increase the stability of active species, improve the ability of catalytic dissociation of hydrogen and activation of carbon dioxide, and is beneficial to the carbon dioxide reduction reaction.
[0115] Test Example 2
[0116] The high surface area amorphous zirconium oxide catalytic materials prepared in Examples 1 to 8, referred to as catalytic materials, were used to perform catalytic hydrogenation of CO2 gas to produce methanol. The flow rate of the CO2+H2 mixed gas was 36.0 mL / min (25 volume % CO2, 75 volume % H2) and the space velocity was 21600 mL / (g cat h) Establish a micro fixed bed simulation reaction system.
[0117] First, the high surface area amorphous zirconia catalytic material prepared in the above embodiments, referred to as catalytic material, was taken 0.1g of the catalytic material prepared in the above embodiments 1 to 8, and mixed with 0.4g of quartz sand respectively, and reduced for 2h in a 10vol% H2 / Ar gas flow at 300°C, and then cooled to ambient temperature; CO2+H2 mixed reactants were introduced and pressurized to 4.5MPa, and then the catalytic performance was evaluated at three different target temperatures of 220, 240 and 260°C; the exhaust components obtained in each group, such as CO, CO2, H2O and CH3OH, were subjected to online quantitative analysis by a gas chromatograph with a thermal conductivity detector, and the test results are shown in Table 2.
[0118] Table 2 Test results of catalytic performance of the catalytic materials prepared in Examples 1 to 8 under different temperature conditions
[0119]
[0120] From the results in Table 2, it can be seen that the catalytic material of the present invention has excellent carbon dioxide conversion rate and methanol selectivity, reflecting excellent catalytic performance for the preparation of carbon dioxide hydrogenation.
[0121] Test Example 3
[0122] The high surface area amorphous zirconia catalytic materials prepared in Examples 1 to 7 were subjected to X-ray powder diffraction (XRD) experiments using a Miniflex 600 XRD diffractometer manufactured by Rigaku. The results are as follows: Figure 1 as shown in .
[0123] Referring to Table 1 and Table 2, Figure 1 It can be seen that after copper doping and H2 / Ar reduction, the amorphous structure of the catalyst carrier is still maintained, and faint crystalline phase peaks of metallic copper (Cu) and cuprous oxide (Cu2O) appear, while the crystalline phase peaks of zinc oxide and gallium oxide are not detected. This shows that amorphous zirconia with a high specific surface area is conducive to the formation of tiny-sized copper, zinc, and gallium nanocrystals or their rich alloy interface species, which significantly improves the material's CO2 catalytic hydrogenation to methanol performance.
[0124] The present invention is not limited to the above examples. Within the scope defined by the claims of the present invention, various deformations or modifications that can be made by those skilled in the art without creative work are protected by this patent.
Claims
1. Application of a high surface area amorphous zirconium oxide catalytic material, characterized in that: It is applied to the catalytic hydrogenation of carbon dioxide to synthesize methanol; The method for preparing the amorphous zirconium oxide catalytic material comprises the following steps: S1, adding zirconium nitrate to ethanol, dissolving it by ultrasonication, and then adding propylene oxide to carry out a first contact reaction to obtain a solution I; in terms of molar ratio, the amount of propylene oxide and zirconium nitrate calculated as Zr element is (1.5-2.5):1; S2, subjecting solution I to a hydrothermal reaction, and drying and crushing the resulting material to obtain amorphous zirconium oxide; S3, adding amorphous zirconium oxide into water, dispersing by ultrasonication, adding a metal copper salt or a combination of a metal copper salt and a metal zinc salt, a metal gallium salt or a metal manganese salt, and performing a second contact reaction to obtain a solution II; S4, adding an aqueous solution of ammonium carbonate to solution II to carry out a third contact reaction. After the reaction is completed, the obtained material is centrifuged, dried, crushed, and calcined to obtain an amorphous zirconium oxide catalytic material with a high surface area.
2. The use according to claim 1, characterized in that: The conditions of the first contact reaction are: temperature of 10-40° C., time of 0.1-10 min; the first contact reaction is carried out under stirring, and the stirring rate is 50-500 rpm.
3. The use according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 100-200°C and the time is 15-25h.
4. The use according to claim 1, characterized in that: In step S3, the conditions of the second contact reaction are: temperature of 10-40°C, time of 0.1-10h; the second contact reaction is carried out under stirring, and the stirring rate is 50-500rpm.
5. The use according to claim 1, characterized in that: In step S4, the conditions of the third contact reaction are: temperature of 70-90° C. and time of 0.1-10 h.
6. The use according to claim 1, characterized in that: In step S2, the drying conditions are: temperature of 40-80°C and time of 2-24h.
7. The use according to claim 1, characterized in that: In step S4, the calcination conditions include: temperature of 300-500° C. and time of 0.5-8 h.
Citation Information
Patent Citations
Zirconium-based arsenic removing material and preparation method and application thereof
CN102068957A